2012
DOI: 10.1111/j.1365-2699.2012.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the chestnut‐tailed antbird (Myrmeciza hemimelaena) clarifies the role of rivers in Amazonian biogeography

Abstract: Aim  We examined patterns of spatial and temporal diversification of the Amazonian endemic chestnut‐tailed antbird, Mymeciza hemimelaena (Thamnophilidae), to evaluate the diversification of a widespread avian taxon across rivers that potentially represent major natural barriers. Location  Lowland Amazonia. Methods  Sequences of the mitochondrial ND2 and cytochrome b genes were investigated from 65 individuals distributed throughout the entire range of M. hemimelaena, and including the two currently valid subsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 64 publications
7
78
1
2
Order By: Relevance
“…This scenario has been shown to be congruent with recent divergence of avian populations across the river (Fernandes et al, 2012;Maldonado-Coelho et al, 2013;Ribas et al, 2012). According to this scenario, the Purus Arch (at 62°W) formed an eastern limit bounding the Solimões wetland system in western Amazonia until 9.5-6 Myr (Latrubesse et al, 2010), when the Amazon River broke through this barrier to drain toward the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 71%
“…This scenario has been shown to be congruent with recent divergence of avian populations across the river (Fernandes et al, 2012;Maldonado-Coelho et al, 2013;Ribas et al, 2012). According to this scenario, the Purus Arch (at 62°W) formed an eastern limit bounding the Solimões wetland system in western Amazonia until 9.5-6 Myr (Latrubesse et al, 2010), when the Amazon River broke through this barrier to drain toward the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 71%
“…Rivers influence animal distributions such as birds (e.g., Fernandes, Wink, & Aleixo, 2012), frogs (Gascon, Lougheed, & Bogart, 1998), and mammals (e.g., Patton, Da Silva, & Malcolm, 2000) that disperse the seeds of palms and other plants. The impact of rivers on the genetic structure of other plants such as Myricaria laxiflora (Tamaricaceae; Liu, Wang, & Huang, 2006) has shown that water flow is a major driver of seed and propagule dispersal, and that migration patterns among populations can form along rivers, similar to what we found here in M. flexuosa .…”
Section: Discussionmentioning
confidence: 99%
“…This formation could have similarly influenced capybaras. The HRCH seems to play a fundamental role in the diversification process of numerous avian taxa [11,[204][205][206][207][208][209] and some Primates taxa [110,210]. The temporal splits obtained with the MNJ procedure could also support the RH, because glacially-driven diversification mainly occurred within the last 0.9-0.02 MYA.…”
Section: Miocene and Pliocene Amazon Biodiversity Hypotheses For The mentioning
confidence: 95%
“…This ''Young Amazon'' model suggests that the current Amazonian drainage system was established between 2-3 Millions of years ago, MYA, and the major Amazonian river tributaries originated within the last 2 MYA. Watershed breakdowns and headwater captures influence the diversity of both aquatic and non-aquatic organisms [11,111,154,205,210] Bolivia which suggests that only Pleistocene biodiversity hypotheses are germane to mitochondrial diversification in capybara.…”
Section: -Uplift Of the Northern Andes In The Latementioning
confidence: 99%